Supply-Side Model of Academic Publishing in Croatia (2012–2018) - Horvat, Filip; Velagić, Zoran (Knygotyra, 2020)
The paper examines and presents the scale and structure of recent (2012–2018) academic publishing in Croatia, with a focus on academic books and journals, the participation of institutions and publishers, scientific fields and disciplines, and invested financial means. As Croatian academic production to a large extent depends on subsidies, the paper is based on the analyses of data from seven years of subventions, which the Croatian Ministry of Sciences and Education allocates to national academic publishers, regardless if they are academic institutions or privately owned publishers. Conducted analyses provide detailed insight into the model of supply-side academic publishing and into national academic publishing in general. The topics – academic publishing and system of subsidies – have rarely been addressed in recent research. Thus, this paper offers new insights for researchers (e.g. providing knowledge about the scale and structure of academic publishing), provides evaluation possibilities for policymakers (e.g. to design the tools for monitoring and improving the system of public subsidies), and provide comparable perspective for national academic publishing in the context of European academic publishing setting.